2002
DOI: 10.1096/fj.02-0125fje
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differential gene expression in stretched podocytes: osteopontin enhances adaptation of podocytes to mechanical stress

Abstract: Glomerular hypertension is a major determinant advancing progression to end-stage renal failure. Podocytes, which are thought to counteract pressure-mediated capillary expansion, are increasingly challenged in glomerular hypertension. Studies in animal models of glomerular hypertension indicate that glomerulosclerosis develops from adhesions of the glomerular tuft to Bowman's capsule due to progressive podocyte loss. However, the molecular alterations of podocytes in glomerular hypertension are unknown. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 37 publications
4
73
0
1
Order By: Relevance
“…Several investigators have reported that the elevated expression of OPN in vasculature has a crucial role in atherosclerotic calcification [6,8,23,30]; however, the significance of whether the enhancement is inducible or preventive to the vascular calcification has not been fully revealed. In addition, recent studies have shown that, in vascular wall cells, the expression of OPN is accelerated by advanced glycation end-products [31] and mechanical stress [32]. Therefore, it might be considered that these findings can be associated with the mechanism(s) of elevating the plasma OPN level by both aging (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Several investigators have reported that the elevated expression of OPN in vasculature has a crucial role in atherosclerotic calcification [6,8,23,30]; however, the significance of whether the enhancement is inducible or preventive to the vascular calcification has not been fully revealed. In addition, recent studies have shown that, in vascular wall cells, the expression of OPN is accelerated by advanced glycation end-products [31] and mechanical stress [32]. Therefore, it might be considered that these findings can be associated with the mechanism(s) of elevating the plasma OPN level by both aging (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Cancer cells produce an FN-rich fibrotic matrix to facilitate metastasis, and both FAK (4, 7) and MYO1E (32) promote carcinogenesis in murine cancer models. In addition, MYO1E protects kidney podocytes from mechanical stressinduced injury, as does SPP1, which may be induced by FAK (33,34). Moreover, keloid formation (i.e., a wound-healing reaction with excessive scar formation) has been associated with MYO1E (35) and FAK function (36).…”
Section: Discussionmentioning
confidence: 99%
“…Many factors that facilitate atherosclerosis, such as hypoxia, high plasma glucose, 27 platelet-derived growth factor, 28 AII, 18,29 aldosterone 8 and mechanical stress, 30 also induce OPN expression. OPN has several effects that may facilitate the development and progression of cardiovascular lesions, including cell adhesion, migration, proliferation, angiogenesis and ectopic mineralization.…”
Section: Discussionmentioning
confidence: 99%